PROSPEK MODEL-KAWASAN RUMAH PANGAN LESTARI (M-KRPL) DAN REPLIKASI PENGEMBANGAN KRPL (Forum Penelitian Agro Ekonomi, 2013)
Food security issues deal with critical problem, namely food demand grows faster than that of production. To achieve food self-sufficiency and food security, the Ministry of Agriculture Indonesia through Indonesian Agency for Agricultural Research and Development develops the Model of Sustainable Food Houses Region (M-KRPL) and its replication, namely the Sustainable Food Houses Region (KRPL). The concept of M-KRPL and KRPL programs needs to be refined primarily due to program design, implementation period, implementing organizations, introduced technologies, and strengthened local institutions. Implementation of M-KRPL and KRPL should be carried out through excellent social process and stages of growth, i.e. growing, developing, maturation, and self-reliance. M-KRPL replication should take account the technology use as well as community empowerment. M-KRPL and KRPL is promising in terms of technical, economic and institutional aspects. Important policy implications are: (a) taking accounts the technical aspect and social-economic characteristics of the targeted groups, (b) program period must be at least three years along with the growth stages; (c) the main M-KRPL and KRPL implementing organizations are the Assessment Institute for Agricultural Technology (AIATs) and Regional governments, respectively; (d) the technology introduced consists of nursery, farm practice, post harvest, and processing; and (e) managerial and capital development.